Gastric Carcinogenesis by Duodenal Reflux Through Gut Regenerative Cell Lineage - Mukaisho, Ken-Ichi; Miwa, Koichi; Kumagai, Hitomi; Bamba, Masamichi; Sugihara, Hiroyuki; Hattori, Takanori (Digestive diseases and sciences, 2003)
To elucidate the histogenesis of gastric stump cancer, we performed an operation in rats to make all duodenal contents flow back into the glandular stomach. The subjects were 41 rats, and sequential morphological changes of the duodenogastric stoma and the incidence of stump cancers were studied. Serial sections around the stoma were studied with mucin stains such as paradoxical concanavalin A (Con A), galactose oxidase Schiff (GOS), and high-iron diamine-Alcian blue (HID-AB). An immunohistochemical study on cell proliferation with bromodeoxyuridine (BrdU) was also done. At week 30, pyloric gland type cells positive for Con A first appeared at the base of the intestinal crypts and the fundic glands adjacent to the anastomosis. These glands became large with time, resulting in formation of cystically dilated glands. These gland cells were partially stained with GOS, and then they retained a proliferative activity. These changes seemed to resemble "gastritis cystica profunda" in human remnant stomachs. At 50 and 80 weeks, adenocarcinomas were observed in 4 of 10 rats (40.0%) and in 16 of 21 rats (76.2%), respectively. We have noted that the early change of cystic proliferation of mucous glands resembled the so-called "ulcer associated cell lineage (UACL)" described by others, but our characteristic finding was not only pyloric but also foveolar metaplasia. This pyloric-foveolar metaplasia subsequently led to development of glands with intestinal-type goblet cells, which looked like incomplete intestinal metaplasia. This sequence was different from UACL, and very recently, we proposed a concept of "gut regenerative cell lineage (GRCL); from pyloric-foveolar to with goblet cell metaplasia in regeneration," common to all parts of the gut, and the stump cancer appeared to arise from GRCL.